The Impact of Utilitarian and Hedonic Values on Hijab Buying Intentions: Evidence from Indonesia - Moh Farid Najib; Tia Fauziah; Tjetjep Djatnika; Dedy Saefulloh; Dewi Purnamasari (Politeknik Negeri Bandung, 2022)
Hijab has become a necessity for Muslim female customers. Hijab products are various as it is not only used as a cover, but it also increases their confidence since hijab fashion does not have to be left behind by non-hijab fashion. The interest in buying a premium hijab may be due to its utilitarian or hedonic nature. This paper aims to examine the differences between the importance of utilitarian and hedonic values on evidence of buying intention of hijab from Indonesia. This research employs explanatory research by collecting 400 Muslim female respondents in West Java. The data processing method uses a scoring with a Likert scale from a score of one to five. The structural Equation Model (SEM) is used to analyze the data by applying SEM-PLS. The results show that both the utilitarian values and the hedonic values simultaneously do not affect the buying intention. Instead, they partially give a significant effect on the buying intention. This means that Muslim women in Indonesia are competing in seeking the values of their faith and need emotional satisfaction in their daily activities.